Diversidad de aves en el campus de la ciudad universitaria ecológica "Zungarococha" de la Universidad Nacional de la Amazonía Peruana, Loreto - Perú - Navarro Estrella, Lesly Almendra (2022)
From june to september 2018 I studied the diversity of birds in the campus de la university city ecological “Zungarococha” of the National Universty of the Peruvian Amazonía, by direct observation, auditive method and mist nets. The composition of birds was conformated by 15 order, 28 families and 64 species, where it orden Passeriformes report 11 familias and 31 species, the Órden Piciformes with 3 familias and 7 species. The relative abundance more high it was for Cacicus cela (7.17 ind/km) and Tachornis squamata (5.26 ind/km). While the density more high (perpendicular distance) was for Brotogeris sanctithomae (13.36 ind/km2), and with Distance were Milvago chimachima and Tyrannus melacholicus with 72.05 y 55.11 ind/km2.. I conclude that the composition of birds in the campus of the university city ecological “Zungarococha” he was conformated by especies of the orden Passeriformes.